“[A]ll comes alive and starts to dance”: The 29th Chapter of Gabriel Josipovici’s Goldberg: Variations - Günther Jarfe (Revue LISA)
This paper tries to determine the meaning and function of chapter 29 of Gabriel Josipovici’s Goldberg: Variations. In several respects, it goes beyond the scope of the rest of the book and cries out for a comment. My thesis is that chapter 29 retells the beginning of the novel in such a remarkably different way in order to convey the certainty of and the delight in a happy outcome of Goldberg’s visit. The evidence presented is twofold. First, there is the dance scene, the significance of which can be inferred from chapters 18 and 27. Both employ “dance” metaphorically to describe the liberating effect of an art form, like the fugue, and of living one’s life creatively. The dancing shows Westfield having finally freed himself from his anxieties and having become “the lord of time.” Second, there is the close correspondence that can be shown to exist between chapter 29 and Bach’s last variation. By combining “singing in canon” and “dancing round the table” and presenting this scene in a very stylized fashion Josipovici tries to create a narrative equivalent to Bach’s quodlibet. Within their respective contexts, both pieces perform a similar function. Just as Bach’s final variation is said to be the crowning achievement of the whole sequence, so chapter 29 may be seen as the successful culmination of the novel.